Day-Ahead Economic Dispatch of AC/DC Hybrid Distribution Network Based on Cell-Distributed Management Mode - Wei, Wei; Hao, Tonglin; Xu, Tao (Frontiers in Energy Research, 2022)
Current development trends suggest that future networks will be AC/DC hybrid distribution networks (AC/DC HDNs) operating under the Cell-distributed management mode (CDMM). Cross-Cell transaction in the economic dispatch of CDMM-based distribution networks is necessary to ensure Cell demand, improve the level of renewable energy generation outpower consumption, and enhance the economic efficiency of the whole system. To realize adjacent Cell and cross-Cell transactions in this management mode, this paper proposes a day-ahead economic dispatch model of AC/DC HDNs based on CDMM. The proposed model includes a power transaction stage and a security check stage. In the power transaction stage, a Cell-to-Cell transaction model based on the alternating direction method of multipliers is established. This model forms a consistent transaction plan between different Cells on the basis of information exchange between the Cell operator and the Cell system operator. In the security check phase, a security check model based on data-driven distributionally robust optimization is developed to reduce the transfer power according to various security considerations. Alternate iteration of these two stages enables the day-ahead economic dispatch of AC/DC HDNs based on CDMM for adjacent Cell and cross-Cell transactions. Finally, the effectiveness of the proposed model is verified through a numerical example. The differences among four dispatch models are analyzed to illustrate the need for cross-Cell transactions, and the impact of the confidence level on the dispatch results is discussed.